Numerical Study on the Rising Motion of Bubbles near the Wall - Kaixin Zhang (MDPI AG, 2021)
Based on the volume of fluid method (VOF), the rising characteristics of bubbles in near-wall static water are studied. In this study, the influence of the wall on the rising motion of the bubble was studied by changing the distance of the bubble wall, the diameter of the bubble, the arrangement of the bubble and the size ratio, etc. The influence is expressed as the average swing amplitude of the “Z”-shaped motion when the bubble rises. The study found that in the case of a single bubble, the wall surface has a certain influence on the rise of the bubble, and its degree is affected by the bubble wall distance and the bubble diameter. The influence of bubble wall distance is more obvious. The greater the bubble wall distance, the less the bubble is affected by the wall; in the case of double bubbles, the influence of the interaction force between the bubbles is significantly greater than the wall surface.